Philosophy of Character Education: A Study on the Conception of A.M. Iqbal - Imam Bahroni (At-Ta'dib, 2011)
No one can develop any intelligent theory of education withoutconsciously postulating some conception of the nature of the individual to beeducated, his relationship to the community and, what may be called, his ultimatedestiny. For, the essence of the educative process, reduced to its most elementaryterms, lies in the fact of a living human organism being in constant interactionand contact with a vast and complex environment, which keeps on changingand growing as a result of this continuous, mutual intercourse. Like thephilosopher, the educator must necessarily inquire into the nature of these twoterms of his activity, the individual and environment which ultimately determinethe solution of all his problems.According to Allama Muhammad Iqbal, there is no universal life.Everything and every being possesses an individuality which its place in theuniverse depends upon the degree of development of this individuality. Evenmatter itself, or not-Self, consists of a colony of Egos of a low order: life andconscience emerge when their association and interaction reach a certain degreeof coordination. Individuality is an ascending movement which takes in itstrain all living beings. This movement goes up the ladder of existence to thepoint of man’s highest development when he becomes a Personality.In educational terms, the character of the good man, the true believer,the Momin, as visualized by A.M. Iqbal is a man who develops all his powersand strengthens his individuality through active contact with his material andcultural environment.